The Causality Relationship between Exchange Rate Protected Deposits and Investment Instruments: Evidence from Türkiye - Saka Ilgin, Kubra; Sercan Sari, Salim (International Journal of Economics, Management and Accounting, 2025)
This paper examines the causality relationship and the sign and magnitude of the relationship between the Exchange Rate Protected Deposit (ERPD) application, which was introduced to prevent the negative trend in exchange rates in Türkiye, and the stock market, exchange rate, and interest rate, which are considered as alternative investment instruments. ISE100 index closing prices, USD and EUR prices, weighted average deposit interest rate, and weekly data for the period 18.02.2022-17.11.2023 were used as the data set. Toda-Yamamoto causality, impulse-response, and variance decomposition analysis were applied. It is determined that the application of the ERPD affects alternative investment instruments and it is affected by them. In addition, it has been determined that the order of magnitude affecting the ERPD is as follows: euro prices, deposit interest rate, stock market index, money supply, and dollar prices. It was determined that the ERPD negatively affected the stock market and deposit interest rates. However, it was concluded that the ERPD application could not achieve the target of decreasing the euro and dollar prices. This paper will contribute to the literature, and it is thought that the results will be useful for policymakers, investors, and similar financial actors who wish to learn about ERPD.